2020
DOI: 10.1136/gutjnl-2019-318237
|View full text |Cite
|
Sign up to set email alerts
|

Cirrhosis as new indication for statins

Abstract: In the recent years, there have been an increasing number of reports on favourable effects of statins in patients with advanced chronic liver disease. These include reduction in portal pressure, improved liver sinusoidal endothelial and hepatic microvascular dysfunction, decreased fibrogenesis, protection against ischaemia/reperfusion injury, safe prolongation of ex vivo liver graft preservation, reduced sensitivity to endotoxin-mediated liver damage, protection from acute-on-chronic liver failure, prevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 106 publications
(127 reference statements)
3
82
0
5
Order By: Relevance
“…These data suggest that patients with aHCC do not have increased susceptibility to hepatotoxicity from statins and these results are consistent with a recent clinical trial in patients with aHCC treated with pravastatin 40 mg [23]. Further, recent observations have shown that patients with liver disease do not have a higher risk of statin-induced liver toxicity when compared to the general population [16,28]. The fact that the combination of sorafenib + pravastatin is safe and displays low toxicity is of pivotal importance in order to further deeply study its potential benefits in patients with HCC (i.e., earlier vs. advanced stages) in the future.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These data suggest that patients with aHCC do not have increased susceptibility to hepatotoxicity from statins and these results are consistent with a recent clinical trial in patients with aHCC treated with pravastatin 40 mg [23]. Further, recent observations have shown that patients with liver disease do not have a higher risk of statin-induced liver toxicity when compared to the general population [16,28]. The fact that the combination of sorafenib + pravastatin is safe and displays low toxicity is of pivotal importance in order to further deeply study its potential benefits in patients with HCC (i.e., earlier vs. advanced stages) in the future.…”
Section: Discussionsupporting
confidence: 89%
“…In line with this, a randomized double-blinded, placebo-controlled Phase II trial will examine the effects of pravastatin use versus placebo after 12 months of treatment on HCC recurrence in patients with liver cirrhosis (NCT03219372). Notably, previous studies and preclinical evidences have assessed the potential beneficial anti-inflammatory and antifibrotic effects of statins as well as the rationale for the use of statins in chronic liver disease including the setting of liver cirrhosis [16,28]. In this regard, the therapeutic efficacy of pravastatin may delay HCC development and should be addressed in these settings in a near future, particularly in patients with early stage disease and/or after tumor resection, during which the effects would probably be even more noticeable.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of statins to treat different conditions have shown beneficial and pleiotropic properties in different chronic diseases, beside and independent of its cholesterol-lowering effects. [120][121][122] Their positive effects are not limited to healthspan amelioration, but to exert antiaging benefits increasing the lifespan in drosophila, mice, and even in humans. [123][124][125][126] Several mechanisms underlie the antiaging effects of statins.…”
Section: Statinsmentioning
confidence: 99%
“…76 Future works should further study its applicability at the bedside, always considering the optimal dose and the subpopulation of aged patients that would mostly benefit from this therapeutic opportunity. 122,133,135 Other drugs like metformin or rapamycin are well-known for their anti-aging effects. Remarkably, the Geroscience Interest Group inside the National Institute on Aging, pointed out that many of these drugs with antiaging effects were clinically approved for treating chronic diseases, and therefore, it would be interesting to screen for other drugs in this category, and test their potential to increase healthspan.…”
Section: Statinsmentioning
confidence: 99%
“…(34)(35)(36)(37) Examples of clinically important PKPD changes in select medications (including PIMs) that occur in patients with cirrhosis are provided in Table 2. (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53) To prevent ADRs due to these changes, health care professionals should carefully select an appropriate medication and dose adjust when prescribing.…”
Section: Pharmacokinetic and Pharmacodynamic Changesmentioning
confidence: 99%